Kepemimpinan Kenabian dalam Pengembangan Pendidikan Karakter Siswa SD IT Assalaam Sanden Kabupaten Bantul - Tomi; Yusuf Atma Suryabudi; Zainal Arifin (Southeast Asian Journal of Islamic Education Management, 2024)
The purpose of education is none other than to shape the character and behaviour of individuals and learning groups in order to have a character spirit in accordance with the norms. In formal education, there has been a moral and moral crisis in students. Prophetic leadership is closely related to the formation of a person's behaviour and character, especially in the context of education that aims to educate and form morals. Prophetic leadership can have a significant impact on school organisations. Prophetic leadership plays an important role in the figure or example of people in the surrounding environment. This research was conducted at the level of Islamic basic education involving principals, teachers, and students related to the implications of the application of prophetic leadership on the development of character education in students. Data collection was done by interview and documentation. The data obtained in the form of exposure to interview information sources are then condensed, analysed and will be verified in accordance with the validity of the data. This study aims to describe the phenomenology of prophetic leadership and its relation to student character education at SD IT Assalaam Bantul. The results of the study explain that the principal in leading educational institutions has implemented prophetic leadership by integrating prophetic traits in its management. With a characterful principal leader, it is able to have a positive influence on the surrounding environment, especially for students, because the principal in the scope of education is a central role model. SD IT Assalaam Sanden Kabupaten Bantul has a programme of development activities that can shape the character of students according to Islamic teachings and uphold Islamic values.